The Syariah's protection of the right to the person vis-a-vis the western law of torts - Abdurrahman, Syed Ahmad Shihabuddin (2009)
The Syari'ah pioneered the protection a person's right to his person, property (including wealth) and reputation. The Holy Qur'an and the sayings of the Prophet s.a.w. clearly protect the sanctity of life, property and honour of every individual, Muslims and non-Muslims.